The interference of Moringa oleifera leaf extracts to modulate quorum sensing-facilitated virulence factors - Suhartono Suhartono; Yulia Sari Ismail; Syarifah Raisha Muhayya (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Suhartono S, Ismail YS, Muhayya SR. 2019. The interference of Moringa oleifera leaf extracts to modulate quorum sensing-facilitated virulence factors. Biodiversitas 20: 3000-3004. The infections attenuated by the presence of virulence factors might be facilitated by quorum sensing (QS) mechanism. The continuous treatments of bacterial infections with current drugs, however, has developed such pathogenic bacteria more antibiotic-resistant, encouraging to searching for better alternative treatment, such as the use of plant-derived bioactive constituents, including kelor (Moringa oleifera L.). In the present research, kelor (M. oleifera) ethanolic leaf extract was evaluated for their potency as an antibacterial agent to inhibit bacterial virulence factors mediated by quorum sensing mechanism against Chromobacterium violaceum and Pseudomonas aeruginosa PAO1. A phytochemical examination of M. oleifera leaf-ethanolic extracts has been conducted resulting positive detection of alkaloids, steroids, terpenoids, flavonoids, and phenolics or tannins. The extracts had MIC and MBC values of 10 mg/mL and 20 mg/mL, respectively, for both tested bacteria. The ethanolic extracts of M. oleifera leaves also showed potent inhibition of quorum sensing by significantly reducing violacein and pyocyanin production as well as interference of swarming motility and biofilm formation.